Workshop on Tourism Service Quality for Tourist Satisfaction and Return Visits to Cikadu Tourism Village, Tanjung Lesung Buffer Zone - Rahmiati, Filda; Nugraha, Rendika; Prayoga, Tasya Zahwa (Asia Pacific Journal of Management and Education (APJME), 2023)
In the light of COVID-19 outbreak, the tourism industry has affected the most with a loss in visitor both in local and foreign. The popularity of village tourism has increased as it can significantly boost the local and regional economies. This study is a explatorary research with descriptive analysis approach takes the form of community service activity program that based on a penta-helix structure and featured a strategic steering stakeholder with the representatives from academics, volunteers, businesspeople, and local resident from Cikadu, Tanjung Lesung. This paper intend to identify the stakeholders involved and increase their knowledge towards penta-helix model in village to rbuild restart tourism. This study found that not all tourism stakeholders in Cikadu village aware of the penta-helix model due to a lack of synergy in maximizing their roles. However, the workshop program giving a positive response from tourism village stakeholder and they are capable using a cooperative strategy between the community and stakeholders to manage tourism during a pandemic. The Penta helix instilled both knowledge and a fervor for tourist village development in participants.